Penerapan Strategi Efisiensi Biaya Endorsement dengan Rate Card dan Engagement Rate dalam Kampanye Influencer CV Avero Indonesia - Putri Nabilah Azahra; Dewi Deniaty Sholihah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
The purpose of this research is to find out the Application of Endorsement Cost Efficiency Strategy with Rate Card and Engagement Rate in CV Avero Indonesia Influencer Campaign, In the growing digital era, marketing through influencers is one of the most effective strategies to reach a wider audience. With quantitative and qualitative research approaches. This implementation method is focused on implementing cost-efficiency strategies in endorsement campaigns by linking rate cards and influencer engagement rates to select the right influencers. On implementation, the use of multiplatforms such as Instagram and TikTok was proven to increase audience reach and engagement. F2 influencers, who utilize both platforms, have a greater impact in expanding audiences and driving engagement. Through influencer data analysis, Cost per views (CPV) calculation, and cost-efficiency based selection, campaigns were conducted on both TikTok and Instagram platforms. This strategy successfully improved marketing effectiveness, expanded audience reach, and maximized budget with measurable results. This data-driven approach demonstrates the importance of cost management in maximizing promotional impact, while strengthening product competitiveness in the market.